Nasturtium officinale Microshoot Culture Multiplied in PlantForm Bioreactor—Phytochemical Profiling and Biological Activity - Marta Klimek-Szczykutowicz; Magdalena Anna Malinowska; Aleksandra Gałka; Ivica Blažević; Azra Ðulović; Paulina Paprocka; Małgorzata Wrzosek; Agnieszka Szopa (Molecules)
Nasturtium officinale R. Br. (watercress) is an endangered species with valuable pharmaceutical, cosmetic, and nutritional properties. The purpose of this work was to evaluate the phytochemical profile and biological activity of extracts from microshoot cultures grown in PlantForm bioreactors and the parent plant material. After 20 days of cultivation, the cultures achieved the best results both in terms of key active ingredient content and biological activity. The glucosinolates (GSL) profile by the UHPLC-DAD-MS/MS method showed that the dominant compounds were glucobrassicin (493.00 mg/100 g DW, 10 days) and gluconasturtiin (268.04 mg/100 g DW, 20 days). The highest total polyphenol content (TPC) was obtained after a 20-day growth period (2690 mg GAE/100 g DW). Among polyphenols, the dominant compounds in the extracts from in vitro cultures were sinapinic acid (114.83 mg/100 g DW, 10 days) and ferulic acid (87.78 mg/100 g DW, 20 days). The highest antioxidant potential assessed by ABTS and DPPH assays was observed for ethanol extracts. The best results for inhibiting hyperpigmentation (18.12%) were obtained for ethanol extracts and anti-elastase activity (79.78%) for aqueous extract from N. officinale microshoot cultures. The extracts from microshoot cultures inhibited the growth of bacteria, including Cutibacterium acnes (MIC = 0.625 mg/mL). Antioxidant tests and the chelating capacity of iron ions Fe2+ of the face emulsion with N. officinale extracts showed higher results than the control.